Implementasi Total Quality Manajemen dalam Meningkatkan Profesionalisme Guru di SMA - Muhamad Abdul Manan (Program Pascasarjana Universitas Ibrahimy, 2017)
Global competition is very tight and makes issues about quality has become a serious studies and discussions among thinkers, practitioners, corporate managers, and education managers. Similarly, what happens in the middle of education in the Islamic boarding school environment. This study focused on the study, How Leadership Principals in the process of the implementation of TQM and how the stages of the learning process undertaken in improving the professionalism of teachers in SMA Ibrahimy Sukorejo Situbondo. This research uses descriptive qualitative research approach because this research is produce the theory in the field and direct researchers come to see the condition of learning. The results of this study describe improvements made by the principal starting from self, building relationships and networking, building the same comitem in the organization, creating a joint control and evaluation system, promoting mutual interest and developing gradual and sustainable quality. As for the improvement of professional teachers starting recruitment, personality development and evaluate the process of teaching and learning activities (KBM).